Interkoneksi Madzhab Filsafat Pendidikan dengan Madzhab Filsafat Pendidikan Islam - Suripto (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2022)
The birth of the scientific discipline of Islamic education stems from a meeting between educational philosophy and Islamic thought. kindly genealogy, the scientific discipline has a point of intersection of paradigms which, if traced to its scientific roots, leads to the study of philosophy as the mother of sciences. Philosophical studies with various variants of madhhab he opened the veils of the scientific spider web (scientific cobwebs) that are interrelated and cannot be separated. The interconnection of thought paradigms between philosophy, educational philosophy, and Islamic thought contributed to the birth of Islamic educational philosophy and thought of the madhhabs. madhhabIslamic educational philosophy of thought perennial-essentialist salafi, perennial-essentialist school of thought, modernist, and perennial-essentialist falsification contextual, and the social reconstruction based on monotheism in this study is the result of a marriage between madhab educational philosophy withmadhhabIslamic thought.